Optimization study of a compressor - Low, Eugene Ya Ming (Nanyang Technological University, 2023)
This report documents the optimization study of a compressor and the process to determine the optimum design of the compressor. The Coupled Vane Compressor is known to be the most compact positive displacement rotary compressor due to its ability to operate with a smaller rotor-to-cylinder ratio. By integrating the compressor simulation model with the MJ box complex optimization algorithm, the optimum design of the Coupled Vane Compressor under a preset objective functions and a set of constraints can be attained. combining the mechanical, volumetric, and isentropic efficiency of the compressor as the objective function to be maximized, while assigning the cylinder and rotor radii as the design variables allowed to vary during the optimum search, the combination of the design variable with optimum objective function can be obtained. By keeping the volume displacement constant at 40cc, the optimum cylinder and rotor radii are 25.008mm and 16.213mm respectively, while the value of the efficiencies that yield the maximum objective function are 73.12%, 77.65%, and 74.41%, with an improvement of 2.78%, 2.35%, and 0.15% from the initial design respectively. This demonstrates that a smaller configuration of the CVC can improve performance while allowing for a more compact design.